Beginning SQL Server 2005 Express for Developers From Novice to Professional - Dewson, Robin (Apress : Imprint: Apress, 2007)
Assuming neither database nor programming background, Beginning SQL Server 2005 Express for Developers introduces all the fundamental database administration and SQL programming features of SQL Server 2005 Express Edition, the free relational database management system from Microsoft that provides a major subset of full SQL Server 2005 functionality. This book is a comprehensive guide that covers installing and configuring SQL Server 2005 Express, creating, backing up, and restoring databases, creating tables, then querying and manipulating them with T-SQL, coding stored procedures and triggers, and using Reporting Services to deliver information to end users. Detailed, clear, and highly readable, this book will make you a competent and confident database administrator and programmer. This is the clearest and most comprehensive introduction to SQL Server 2005 Express. The book assumes no prior experience with databases, SQL, or programming. Youll learn about both database administration and T-SQL programming. The book covers SQL Server Management Studio and Reporting Services.